The quality of nursing care of the frail aged in selected institutions in Eastern Cape and Natal - Noelle B. Hunt; Leana R. Uys (AOSIS, 1990)
An investigation was undertaken to establish standards for the care of the frail aged and to develop an instrument to measure this care. In this process the care in 12 institutions was monitored. In general, the care was found to be o f good quality, with an average o f 74,3%, but there are residences where the percentage is up to 10% lower. The influence o f some internal and external factors on the quality o f care were investigated.